Prevalence of Helicobacter Pylori Among Outpatients at Al-Khadra Hospital, Tripoli: A Cross-Sectional Study (Derna Academy Journal for Applied Sciences, 2025)
Background: Helicobacter pylori is one of the most common chronic bacterial infections worldwide and is strongly associated with gastritis, peptic ulcer disease, and gastric cancer. (Hooi JKY, et al.2017)‎. Objective: To estimate the prevalence of H. pylori among outpatients at Al-khadra Hospital in Tripoli, Libya, and to identify associated epidemiological and clinical risk factors.Methods: Cross-sectional study (July–September 2025) of 100 adults; demographics and symptoms recorded; stool antigen tests used for diagnosis.  Results: Overall prevalence was 46% (95% CI: 36.0–56.3). Infection was significantly associated with smoking (p=0.01) and epigastric pain (p=0.03), but not with gender or age ≥40 years. Conclusion: H. pylori remain a considerable public health burden in Tripoli; findings support early diagnostic and eradication strategies.